Effectiveness of Interactive Learning Strategies in Improving Clinical Reasoning Skills Among Undergraduate Medical Students - Syed Abdullah Faiz, Sadia Majeed, Shazia Inam, Tayyeba Iftikhar Mirza, Ayesha Aleem Qureshi, Noreen Farid (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Clinical reasoning is a critical competency in medical education, enabling future physicians to make accurate diagnoses and management decisions. Traditional didactic methods often fail to actively engage students in this cognitive process. Objectives: To evaluate the effectiveness of interactive learning strategies in improving clinical reasoning skills among undergraduate medical students. Study Design & Setting: This study was conducted at the Department of Medical Education of Foundation University Islamabad involving undergraduate medical students across all years of study. Methodology: A total of 120 students were enrolled and randomly divided into two groups: Group A (n=60, traditional lecture-based learning) and Group B (n=60, interactive learning strategies). Demographic data including age, gender, year of study, prior clinical exposure, and previous participation in reasoning workshops were recorded. Pre- and post-intervention assessments were conducted using a validated Clinical Reasoning Skills Questionnaire (CRSQ) along with objective structured clinical examination (OSCE) stations. Data were analyzed using SPSS v25. Results were expressed as mean ± SD for continuous variables and frequency/percentage for categorical variables. Paired and independent t-tests along with chi-square tests were applied, with p < 0.05 considered statistically significant. Results: Of the 120 students, mean age was 21.6 ± 1.8 years with 55% females. Group B showed significantly higher post-intervention CRSQ scores (72.4 ± 8.5) compared to Group A (61.8 ± 7.9; p < 0.001). Improvement was consistent across gender, study year, and prior clinical exposure. Interactive learning was also associated with higher OSCE performance (78.9 ± 9.2 vs. 66.5 ± 8.7; p < 0.001). Conclusion: Interactive learning strategies are more effective than traditional lecture-based methods in improving clinical reasoning skills among undergraduate medical students. Incorporating such methods into medical curricula may foster better clinical competence. Keywords: Clinical Education, Clinical Reasoning, Interactive Learning, Medical Students, Problem-Based Learning, Simulation